Enhancing board effectiveness : institutional, regulatory, and functional perspectives for developing and emerging markets - Ngwu, Franklin N., 1975-; Osuji, Onyeka; Ogbechie, Chris (Routledge studies in corporate governance., 2019)
Enhancing Board Effectiveness seeks to examine the conceptualization and role of the board in a variety of contexts and articulate solutions for improving the effectiveness of the board, especially in developing and emerging markets. Enhancing Board Effectiveness with therefore address the following central questions: To what extent is the concept and role of the board evolving? What rights, powers, responsibilities and other contemporary and historical experiences can enhance the effectiveness of the board, especially in the particular contexts of developing and emerging markets? What socio-economic, political, regulatory and institutional factors/actors influence the effectiveness of the board and how can the policies and practices of such actors exert such influences? In what ways can a reconstructed concept of the board serve as a tool for theoretical, analytical, regulatory and pragmatic assessment of its effectiveness? In examining this issues, Enhancing Board Effectiveness will investigate theoretical, socio-economic, historical, empirical, regulatory, comparative and inter-disciplinary approaches. Academics in the relevant fields of accounting, behavioural psychology/economics, development studies, financial regulation, law and management/organizational studies, political economy and, public administration will find this book of high interest.